Male and female students' mathematical reasoning skills in solving trigonometry problems - Suparman Suparman; Al Jupri; Edwin Musdi; Nonong Amalita; Maximus Tamur; Jihe Chen (Beta: Jurnal Tadris Matematika, 2021)
[English]: Several studies have examined mathematical reasoning skills (MRS) of male and female students in various mathematics topics. However, there were still not many studies, which focus on MRS in trigonometry topics in terms of gender perspectives. Therefore, this quantitative study aims to describe and compare the MRS of male and female students in solving trigonometry problems. This study involved secondary school students who were given an MRS test. The test has been validated theoretically and empirically. The results of the test were classified using the rubric of MRS achievement and analyzed using the Mann-Whitney test or t-test. The results revealed that the overall MRS of male and female students was low. The students lacked skills in finding a relationship pattern, proposing a conjecture, and generalizing the statement, but they had moderate skills in verifying the truth of an argument. Furthermore, the male and female students were not significantly different in the aspects of MRS. The findings provide important starting points to enhance students' MRS in the teaching and learning of trigonometry. [Bahasa]: Beberapa studi sudah dilakukan untuk menguji kemampuan penalaran matematis siswa laki-laki dan perempuan di berbagai topik matematika. Namun, studi-studi yang fokus pada kemampuan penalaran matematis di topik trigonometri ditinjau dari perspektif gender masih belum banyak. Penelitian kuantitatif ini bertujuan untuk mendeskripsikan dan membandingkan kemampuan penalaran matematis siswa laki-laki dan perempuan dalam menyelesaikan masalah-masalah trigonometri. Studi ini melibatkan siswa sekolah menengah yang diberi tes kemampuan penalaran matematis. Tes tersebut sudah divalidasi secara teoritis dan empiris. Hasil tes tersebut dikategorikan menggunakan rubrik capaian penalaran matematis dan dianalisis menggunakan uji Mann-Whitney atau uji t. Hasil menunjukkan bahwa secara keseluruhan kemampuan penalaran matematis siswa laki-laki dan perempuan belum tinggi. Siswa tersebut kurang mampu dalam menemukan pola hubungan, mengajukan dugaan, dan mengeneralisasi pernyataan, tetapi mereka memiliki kemampuan yang sedang dalam memverifikasi kebenaran suatu argumen. Selanjutnya, siswa laki-laki dan siswa perempuan tidak berbeda secara signifikan dalam aspek kemampuan penalaran matematis. Temuan ini memberikan titik awal yang penting untuk meningkatkan kemampuan penalaran matematis siswa dalam pembelajaran trigonometri.